Intensive Rearing of Juveniles of cichlasoma managuense (Günther 1869) in recirculated systems (ESP) - Günther Nonell, Jorge (1991)
The growth performance of guapote juveniles in recirculated systems from spawning to a mean weight of about 3 gramms is described. Culture began with a 15 days nursing phase with either first instar-nauplii or fresh decapsulated cysts of Artemia followed by artificial diet. Regression models are given for various growth and dispersion parameters. The growth performances with  Artemia nauplii or cysts in the nursing phase are compared.